Fuels from oils and fats: Recent developments and perspectives. Issue 11 (22nd September 2015) - Mittelbach, Martin
Abstract : Fats and oils continue to be the main feedstock for alternative transport fuels, especially for FAME (biodiesel) production. Nevertheless, hydrotreated vegetable oils (HVO), which are mixtures of alkanes, are also established as a commercial fuel. This review describes recent developments in FAME and HVO production and utilization, including microbial oil use. However, the use of unmodified plant oil as fuel or their corresponding engine and emission tests are not discussed. Recent developed catalysts are described for FAME production, including heterogeneous catalysts, such as super acids, ion‐exchange resins, and other green catalysts produced from biomass. Bio‐catalytic approaches using soluble or immobilized enzymes are at the early commercialization stage. Since HVO production technology is based mainly on current mineral oil industry processing methods, the scientific literature is not as extensive as that of FAME production. The main reaction routes of HVO are a combination of hydrogenation, decarboxylation, decarbonylation, hydroisomerization, and cracking under high pressure and temperatures, using supported and unsupported heterogeneous metal catalysts. Recent reports have highlighted the potential use of non‐food oils, such as microalgae lipids, but industrial significant progress has not occurred, leading to some disillusionment with this approach. Therefore, a clear strategy should be developed for upstream and downstream processes with parallel evaluation of life cycle assessment (LCA). In addition, energy intensive steps of biomass drying and solvent extraction should be avoided by using intelligent technologies, such as in situ processing of wet biomass. Biodiesel and hydrotreated vegetable oils today are the most important alternative diesel fuels in the transport sector. They are produced from the same feedstock, namely oil and fat containing biomass. There has been a shift from food sources to waste material like used cooking oil and animal fat residues as well microbial oils. The latest developments in new feedstock sources, process technologies as well as life cycle assessment and future perspectives are discussed. Abstract : Biodiesel and hydrotreated vegetable oils today are the most important alternative diesel fuels in the transport sector. They are produced from the same feedstock, namely oil and fat containing biomass. There has been a shift from food sources to waste material like used cooking oil and animal fat residues as well microbial oils. The latest developments in new feedstock sources, process technologies as well as life cycle assessment and future perspectives are discussed.